FDT Perimetry for Glaucoma Detection in Comprehensive Health Checkup Service. (1st April 2020) - Terauchi, Ryo; Wada, Takashi; Ogawa, Shumpei; Kaji, Masanobu; Kato, Tomohiro; Tatemichi, Masayuki; Nakano, Tadashi
Abstract : We aimed to investigate the efficacy of frequency doubling technology (FDT) perimetry for glaucoma detection in comprehensive screening examinations. We performed a retrospective analysis of prospectively collected data of participants who underwent a comprehensive health checkup service. Participants with glaucoma were excluded. In the first year, 2024 participants (46.8 ± 9.4 years) who underwent FDT perimetry and fundus photography were classified as the FDT group, whereas 3052 participants (42.2 ± 8.2 years) who underwent only fundus photography were classified as the non-FDT control group. Participants with abnormal findings on FDT perimetry and/or fundus photography were recommended to undergo further complete examination. All participants reported whether they had been newly diagnosed with glaucoma within 2 years of the first visit. In the FDT group, 23 (1.14%) participants were newly diagnosed with glaucoma. Among them, 20 (87.0%) had abnormal FDT perimetry findings and 12 (52.2%) had abnormal findings on fundus photography. The positive-predictive value (PPV) of FDT perimetry was 16.5% (20/121) and that of fundus photography was 13.3% (12/90). In participants with abnormal findings on both tests, the PPV was 26.2%. In the non-FDT group, 15 (0.49%) participants were newly diagnosed with glaucoma. Among them, 9 (60.0%) had abnormal findings on fundus photography. The PPV of fundus photography was 10.8% (9/83). The glaucoma detection rate, analyzed using age adjustment, was significantly higher in the FDT group than that in the non-FDT group (0.97% versus 0.47%, P = 0.041 ). FDT perimetry, even if performed by nonspecialized physicians, could improve glaucoma detection when used in addition to fundus photography. This study was registered with UMIN000037951.